Phosphorus removal from municipal wastewater through a novel Trichosporon asahii BZ: Performance and mechanism. (July 2022) - Han, Junli; Qiu, Qi; Gao, Mingchang; Qiu, Liping; Wang, Yan; Sun, Shaofang; Song, Dan; Ma, Jun
Abstract: A yeast BZ was screened from a laboratory-scale anaerobic/aerobic reactor and designated as Trichosporon asahii through 26S rDNA gene sequence analysis. The screened BZ abated over 70% of phosphorus in municipal sewage with 2–10 mg/L phosphorus in the appropriate conditions. The yeast BZ had strong adaptability to pH and the dissolved oxygen, but the cultivation temperature, carbon source, the ratio of C/P and the ratio of N/P had a critical influence on the phosphorus abatement performance of yeast BZ. The analysis of phosphorus concentration in the wastewater, cells, and extracellular polymeric substances (EPS) suggested that about 55%–66% of the removed phosphorus was in the yeast cells and 34%–45% in the EPS. The proposed probable metabolic mechanism of phosphorus in yeast BZ showed that EPS acted as a dynamic phosphorous transfer station, and most of phosphorus was transferred into yeast cells through EPS transfer station. These findings have crucial implications for the development of a promising stable and easy-operation biological phosphorus abatement process for municipal wastewater treatment. Graphical abstract: Image 1 Highlights: A novel yeast strain capable of phosphorus removal was identified. Yeast BZ removed efficiently phosphorus under conventional municipal sewage conditions. The removed phosphorus was mainly stored in yeast cells. The transformation mechanism of phosphorus in yeast BZ was proposed.